Deficiency of MST1 in endometriosis related peritoneal macrophages promoted the autophagy of ectopic endometrial stromal cells by IL-10 - Huang, Yufei; Yan, Shumin; Dong, Xiaoyu; Jiao, Xue; Wang, Shuang; Li, Dong; Wang, Guoyun (Frontiers in Immunology, 2022)
Changes in the function of peritoneal macrophages contribute to the homeostasis of the peritoneal immune microenvironment in endometriosis. The mechanism by which ectopic tissues escape phagocytic clearance by macrophages to achieve ectopic colonization and proliferation is unknown. The expression of CD163 in peritoneal macrophages in patients with endometriosis is increased, with the overexpression of MAPK, which can promote the M2-type polarization of macrophages and reduce their ability to phagocytose ectopic endometrial cells. As an upstream regulator of MAPK, MST1 expression is deficient in peritoneal macrophages of patients with endometriosis. This process is regulated by miR-887-5p, a noncoding RNA targeting MST1. Moreover, MST1-knockout macrophages secrete anti-inflammatory factor IL-10, which promotes autophagy of ectopic endometrial stromal cells. These results suggest that MST1 deficient macrophages may accelerate the autophagy of ectopic endometrium via IL-10 which was regulated by miR-887-5p.